The Role of Work Engagement in Mediating Organizational Support on Lecturer Performance (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2026)
This study examines the influence of Organizational Support and Work Engagement on Lecturer Performance in higher education institutions. Using a quantitative descriptive approach and Structural Equation Modeling (SEM), the research analyzes data from 190 respondents, comprising lecturers from various universities in Medan. The results show that Organizational Support has a significant positive effect on Lecturer Performance with a path coefficient of 0.265, a T statistic of 5.87, and a P value of 0.000, indicating a strong and highly significant impact. On the other hand, Work Engagement also positively affects Lecturer Performance, with a path coefficient of 0.107, a T statistic of 2.977, and a P value of 0.001, which is significant but with a smaller effect compared to Organizational Support. The R-squared value for Organizational Support is 0.656, indicating that 65.6% of the variance in Organizational Support is explained by the model. The findings highlight the importance of organizational support in fostering a productive academic environment, leading to improved lecturer performance. This research provides practical insights for higher education institutions aiming to enhance teaching quality and academic outcomes.